Projeto de aplicação de software para efetivação da comunicação em língua inglesa entre não-nativos, nativos e máquinas utilizando a metodologia do MCE e MMEEBB aplicada ao Globish - Carneiro, Iolanda Borges (2017)
This paper presents a proposal for the application of software that collaborates to establish communication in English between non-native and native speakers and between non-native speakers and machines, based on the fact that 88% of people in the world do not have English as a language maternal. The software will have the programming defined to apply new methodology approaches presented in this work: the Structured Knowledge Maps (MCE) and the Method of Effective Exponential Memorization in the Binary Base (MMEEBB), used to Globish, a simplified variation of English. In this way, it is presented, in this study, some peculiarities of the language (English) that are difficult for non-native speakers, as: aspiration of words, sound schwa and the use of operators and verbs. For the validation of the software was developed in the research process an application which not only addresses the recognition of English, but can contribute to determine the best technical adjustments of the Globish and Cockney, a variant of British English, in such a way communication between humans (native and non-native) and between human-computer (cellular, IoT, learning machines).